Prevention and management of bortezomib-induced peripheral neuropathy in patients with multiple myeloma - S. V. Semochkin; M. V. Solovyev; L. P. Mendeleeva (Онкогематология, 2022)
Proteasome inhibitors and immunomodulators (IMiDs), primarily bortezomib and lenalidomide, are essential components of treatment for both newly diagnosed and relapsed/refractory multiple myeloma (MM), producing high response rates and resulting in improved overall survival. However, bortezomib often induces a dose-limiting toxicity in the form of peripheral neuropathy (PN). Neurotoxicity often affects patient’s quality of life and requires dose modification or withdrawal of therapy, with a possible effect on the overall response. A prompt recognition of predisposing factors (such as diabetes mellitus, vitamin B12 deficiencies, or viral infections) and appearance of signs and symptoms, through a periodic neurological assessment with appropriate scales, is extremely important. Usually, bortezomib-induced PN is a sensory axonopathy characterized by numbness, tingling, and severe neuropathic pain in stocking and glove distribution while motor neuropathy is less frequently observed. Dose adjustment of bortezomib could be necessary during treatment. Anticonvulsants (pregabalin, gabapentin, carbamazepine, etc.) and tricyclic antidepressants (amitriptyline) are most often used to relieve neurological pain. In this review we focus on the clinical manifestations of bortezomibinduced PN, current understanding of the pathophysiological mechanisms as well as clinical and pharmacological aspects of prevention and management this complication. New proteasome inhibitors such as ixazomib and carfilzomib do not have the neurotoxicity of bortezomib. An early switch within the class of proteasome inhibitors from bortezomib to oral ixazomib appears to be an important approach to prevent severe PN. Our own clinical case of an early switch from bortezomib-based induction to IRd triplet (ixazomib, lenalidomide, dexamethasone) is cited as an illustration of the success of this approach.